Teaching Practices in Biology, History, and Geography, from Plants ritualistic and medicinal rituals used in Umbanda terreiro in southeastern Brazil - Souza, Romulo Wagner Oliveira de; Duarte-Silva , Erica (Seven Editora, 2024)
The starting point of the present research is to know the medicinal and ritualistic plants of the Umbanda terreiro in São Mateus-ES. As this is an anthropological research, there is this starting point but the arrival point cannot be predicted. Umbanda is an Afro-American, and Afro-Brazilian, marginalized religion that underwent a process of Christianization when its practicing people arrived on Brazilian soil. Based on this, it is an “outside” cultural practice of Western Christian scientific knowledge, and it is also a marginalized reality. The specific objectives are: (1) To carry out a survey of plant species in the Umbanda terreiro; (2) Carry out a survey of plant species of a ritualistic nature; (3) Build a witness collection of useful plants from the Umbanda terreiro through exicatas, dried herbs and a live collection in pots; (4) Investigate the biological name from the common name collected, and the origin of the plant; (5) Develop interdisciplinary teaching practices in History, Geography and Biology from the knowledge collected; (6) Interview religious leaders of the Umbanda terreiro to learn about the plants used, common name, part of the plant used and how it is used. As methodological paths we will use the ethnography of school practice or anthropology of non-anthropologists for educational purposes; Malinowski’s participant observation; Geertz’s unstructured interviews; ethnographic reports and content analysis. For ethnobotanical work, the Hanazaki methodology will be used. For the preparation of teaching practices, the work will be based on Freire, Romão and Duarte-Silva. DOI:https://doi.org/10.56238/sevened2024.009-016